Transformation Education System and Challenges and Opportunities in the 21st Century - Kurniawan, Satunggale (STAI Nurul Islam Mojokerto, 2025)
The 21st century has bring change big in various aspect life, including in system education. Transformation system education become a inevitability for respond global challenges, progress technology, and dynamics need competence century. This article discuss in a way deep about challenges and opportunities in the process of transformation education, with highlight the need adjustment curriculum, methods learning, the role of teachers, and supporting digital infrastructure. Challenges faced​ covering gap access education, lack of digital literacy among educators and participants educate, and resistance to change the system that has been established. On the other hand, the opportunities that arise covers integration technology in learning, improvement global collaboration, as well as birth approach more learning​ flexible, personal and based competence. With approach interdisciplinary and participatory, transformation education must directed at the formation of individuals who do not only speak in aspect cognitive, but also has skills 21st century like think critical thinking, collaboration, communication, and creativity. The role of government, institutions education, society and business world become very important in support transformation this is to create system inclusive, adaptive and sustainable education. This article ended with recommendation strategic for strengthen policy proactive and responsive education​ to challenges of the times, as well as importance innovation sustainable in development source Power superior Indonesian people.